Pengaruh Inovasi Produk terhadap Peningkatan Daya Saing UMKM Kuliner di Kota Pangkalpinang - Romadia, Romadia; Floryan, Floryan; Mahendra, Fazaldi; Noviyanti, Indah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
MSMEs are a sector that plays a vital role in driving the wheels of the economy, both at the national and regional levels. MSMEs are considered capable of absorbing a large number of workers, increasing community income, and actively contributing to reducing economic disparities. The aim of this study is to understand the influence of product innovation on the competitiveness of culinary MSMEs in Pangkalpinang City. This study focuses on quantitative research using data collection methods through the distribution of questionnaires. The sample in this study was determined using the Slovin formula with a total of 100 respondents, employing a non-probability sampling method with an accidental sampling technique. The collected data were analyzed using simple linear regression with the independent variable being product innovation and the dependent variable being the competitiveness of MSMEs. Based on the results of data analysis, it can be concluded that product innovation has a positive and significant effect on enhancing the competitiveness of culinary MSMEs in Pangkalpinang City.